IDENTIFICATION OF INFLUENCING FACTORS ON THE UTILIZATION OF SURAT BERHARGA SYARIAH NEGARA (SBSN) AS AN ALTERNATIVE FINANCING SOURCE FOR INFRASTRUCTURE PROJECTS IN INDONESIA - Akmal, Bariq
Infrastructure development in Indonesia is a key aspect in accelerating national economic growth and equity. According to the National Medium-Term Development Plan (RPJMN) 2020-2024, the Indonesian government requires a total investment of IDR 6,445 trillion to realize its infrastructure development plans. However, the government's ability to finance this development through the state budget (APBN) and regional budget (APBD) amounts to only IDR 2,385 trillion, or 37% of the total need. Therefore, there is a financing gap of IDR 2,707 trillion that needs to be bridged. To address this gap, the government has utilized various alternative financing sources, one of which is the State Sharia Securities (SBSN). Since its first use for infrastructure project financing in 2013, the issuance of SBSN has shown a significant upward trend. Based on the Central Government Financial Report (LKPP) data from 2013 to 2023, the issuance of SBSN increased from IDR 777.8 billion in 2013 to IDR 34,348 trillion in 2023. This increase indicates that SBSN has become a significant financing instrument in supporting infrastructure development in Indonesia. With the total issuance growing annually, SBSN not only helps reduce the financing gap but also proves to be an effective and reliable alternative financing source. This study aims to identify the factors influencing the utilization of SBSN as a financing source for infrastructure projects in Indonesia and determine the key factors that have the greatest impact on its utilization. The research methods used include a literature review of government publications, financial reports, and scientific journals, as well as surveys through questionnaires and interviews with SBSN stakeholders in Indonesia. The analysis is conducted using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) approach to identify the strengths, weaknesses, opportunities, and threats in the utilization of SBSN. Based on the literature, there are 34 factors influencing the utilization of SBSN: 9 strength factors, 5 weakness factors, 12 opportunity factors, and 8 threat factors. Through the dissemination of questionnaires to determine the relevance of these factors to the SWOT aspects, and based on a series of calculations, these factors were summarized into 25 factors: 9 strengths, 1 weakness, 11 opportunities, and 4 threats. From the 25 identified factors, a further dissemination of questionnaires was conducted to determine the most influential factors from the respondents' perspectives, and the Pareto analysis was used to determine the most significant key factors. The Pareto analysis revealed that out of 9 strengths, 6 factors have the greatest impact; from the 1 weakness, the factor remains significant; from the 11 opportunities, 7 factors have the greatest impact; and from the 4 threats, 3 factors have the greatest impact. These key factors include the intrinsic characteristics of SBSN, internal government policies, and the capacity and competence of the institutions involved in the utilization of SBSN as a financing source for projects or activities. helps reduce the financing gap but also proves to be an effective and reliable alternative financing source. This study aims to identify the factors influencing the utilization of SBSN as a financing source for infrastructure projects in Indonesia and determine the key factors that have the greatest impact on its utilization. The research methods used include a literature review of government publications, financial reports, and scientific journals, as well as surveys through questionnaires and interviews with SBSN stakeholders in Indonesia. The analysis is conducted using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) approach to identify the strengths, weaknesses, opportunities, and threats in the utilization of SBSN. Based on the literature, there are 34 factors influencing the utilization of SBSN: 9 strength factors, 5 weakness factors, 12 opportunity factors, and 8 threat factors. Through the dissemination of questionnaires to determine the relevance of these factors to the SWOT aspects, and based on a series of calculations, these factors were summarized into 25 factors: 9 strengths, 1 weakness, 11 opportunities, and 4 threats. From the 25 identified factors, a further dissemination of questionnaires was conducted to determine the most influential factors from the respondents' perspectives, and the Pareto analysis was used to determine the most significant key factors. The Pareto analysis revealed that out of 9 strengths, 6 factors have the greatest impact; from the 1 weakness, the factor remains significant; from the 11 opportunities, 7 factors have the greatest impact; and from the 4 threats, 3 factors have the greatest impact. These key factors include the intrinsic characteristics of SBSN, internal government policies, and the capacity and competence of the institutions involved in the utilization of SBSN as a financing source for projects or activities. The conclusion of this study is that although SBSN has become a significant financing instrument, there are still several factors that need to be improved to maximize its utilization. This study provides recommendations for policymakers to enhance internal policy structures, improve the capacity of relevant institutions, and strengthen macroeconomic stability to increase the effectiveness of SBSN utilization. The implementation of more structured policies and the enhancement of the competencies of relevant institutions are expected to improve the efficiency of SBSN fund utilization and reduce the gap between budget allocations and the actual absorption of funds.